2018
DOI: 10.3389/fphar.2018.00357
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol, a Polyphenol Natural Compound, Attenuates Cisplatin-Induced Acute Cytotoxicity in Renal Epithelial Cells Through Cellular Oxidative Stress and Cytoskeleton Modulations

Abstract: Cisplatin is a potent anti-cancer drug that has been widely used in the treatment of various cancers; however, cisplatin administration results in severe nephrotoxicity and impedes its clinical applications. In this study, we showed that honokiol, a polyphenol constituent extracted from Magnolia officinalis exhibited a short-term protective effect against cisplatin-induced damages in renal epithelial cells in vitro. The protective effects of honokiol were resulted from the combination of (1) reduced cellular o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
0
13
1
Order By: Relevance
“…Moreover, RNAseq analysis using testicular samples from in-vivo experiments was also performed to evaluate mitochondrial antioxidation enzyme activities. Unexpectedly, unlike our earlier report in the kidney [ 17 , 18 ], TAC assay did not show significant changes between groups ( Figure 4 A); however, from RNAseq analysis, mitochondrial antioxidant enzymes including glutathione peroxidase (Gpx), thioredoxin reductase (Txnrd), glutaredoxin (Glrx), peroxiredoxin (Prdx) were downregulated upon cisplatin treatment, and were upregulated when nHNK was given as treatment ( Figure 4 B). These data suggested cisplatin and nHNK altered mitochondrial enzymatic machinery in the testis.…”
Section: Resultscontrasting
confidence: 81%
See 2 more Smart Citations
“…Moreover, RNAseq analysis using testicular samples from in-vivo experiments was also performed to evaluate mitochondrial antioxidation enzyme activities. Unexpectedly, unlike our earlier report in the kidney [ 17 , 18 ], TAC assay did not show significant changes between groups ( Figure 4 A); however, from RNAseq analysis, mitochondrial antioxidant enzymes including glutathione peroxidase (Gpx), thioredoxin reductase (Txnrd), glutaredoxin (Glrx), peroxiredoxin (Prdx) were downregulated upon cisplatin treatment, and were upregulated when nHNK was given as treatment ( Figure 4 B). These data suggested cisplatin and nHNK altered mitochondrial enzymatic machinery in the testis.…”
Section: Resultscontrasting
confidence: 81%
“…Besides forming DNA adducts [ 6 ], cisplatin also induces excessive ROS production that disrupts physiological balance of redox and anti-oxidation activities [ 42 ]. We previously showed both in vitro and In Vivo that cisplatin compromised mitochondria total antioxidant capacity, and as a consequence, led to imbalanced mitochondria redox processes and caspase 3-associated apoptosis [ 17 , 18 ]. Other studies also showed cisplatin induced dose-dependent testicular damage, ROS generation and ER stress in rat testis [ 10 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study shows that salvianolic acid A inhibits renal cytoskeletal dysfunction through inhibiting the AGE–RAGE signaling, thus effectively ameliorating early-stage DN [44]. The polyphenol honokiol counteracts with cisplatin-induced cytoskeletal structure disruption in renal epithelial cells and preserves epithelial cell polarity and morphology [45]. Our previous study found that chrysin, a naturally-occurring flavonoid, inhibited AGE-induced kidney fibrosis in renal mesangial cells and diabetic kidneys through inhibition of AGE–RAGE activation, contributing to blockade of glucose-mediated AGE-associated glomerulosclerosis and fibrosis [34].…”
Section: Discussionmentioning
confidence: 99%
“…47 HNK was shown to alleviate cytotoxic damages of renal epithelial cells by promoting actin and tubulin polymerization and tubulin bundle formation. 50 This suggested that HNK may contribute to enhanced cytoskeletal integrity by inhibiting HDAC6. Moreover, our current evidence is reminiscent of our previous results obtained using tubastatin A, the well-established HDAC6 inhibitor.…”
Section: F I G U R Ementioning
confidence: 99%